High-Throughput Screening of Antimicrobial Resistance Genes and Their Association With Class 1 Integrons in Urban Rivers in Japan - Kasuga, Ikuro; Nagasawa, Kyoka; Suzuki, Masato; Kurisu, Futoshi; Furumai, Hiroaki (Frontiers in Environmental Science, 2022)
Antimicrobial resistance (AMR) is a serious public health concern. Many countries have implemented AMR surveillance programs for humans and animals, but a scheme for monitoring AMR in the environment has not yet been established. Class 1 integrons, which can acquire antimicrobial resistance genes (ARGs) to gene cassettes, were proposed as a candidate to evaluate the anthropogenic impacts on AMR. However, the association between class 1 integrons and ARGs in aquatic environments is less studied and requires further elucidation. This study used high-throughput quantitative polymerase chain reaction (HT-qPCR) to characterize the pollution profiles of ARGs and mobile gene elements (MGEs) in 24 urban rivers in Tokyo and its surrounding area. The abundance of class 1 integron-integrase gene (intI1) and the array of class 1 integron gene cassettes were also determined. In total, 9–53 target genes were detected per sample, and their abundances increased following effluent discharge from wastewater treatment plants. The river and wastewater samples were categorized based on their HT-qPCR profiles, indicating that this method was useful for characterizing the pollution status in aquatic environments. The prevalence of intI1 in the rivers was observed. Some ARGs and MGEs were positively correlated with intI1, indicating that intI1 could be used as a proxy for monitoring these ARGs and MGEs in urban rivers. Long-read sequencing of class 1 integron gene cassettes revealed that one to three ARGs were present in the gene cassettes. Regardless of the sample type, blaGES-24, aadA2, and qacH were dominant in the gene cassettes. The source and spread of class 1 integrons carrying these ARGs in aquatic environments should be further monitored.